QUALITY ASSESSMENT OF A USER INTERFACE BASED ON THE MENTAL TIME OF PERFORMING THE USER TASKS OF THE SUBJECT AREA - V. K. Grigoriev; A. S. Ilyushechkin; M. A. Ovchinnikov (Российский технологический журнал)
The overall development of information systems and their increasingly significant impact on all areas of the society expressed in such terms as "information society", etc., determines the increasing importance of user interfaces. Moreover, the quality and adequacy of the interface to the tasks of the subject area becomes the determining parameter when choosing a specific organization software product for computer support of the organization. The study of user interfaces involved with the 70s of the last century. Some methods of interface quality research, in particular, the GOMS method is used to date. However, the use of advanced training technology for mass professional users of information systems for the study of interfaces allows to effectively evaluate the interface in the learning process without using the GOMS method. This article is devoted to this issue. The article deals with the method of quantitative evaluation of the quality of the user interface in the form of such characteristics as errors and mental time of the tasks of the subject area. The structure of time of performing tasks of the subject area is analyzed. Mental time is allocated as the characteristic that chiefly determines the usability of the user interface. Mental time is based on the total time of the step, the calculation time at this step, and the mechanical time required for a person to perform an action that causes the step to be performed. It is shown that the use of anticipated training technology of mass professional user can significantly simplify the allocation of mental time by eliminating the time of the task computer. In the structure of time, the mechanical time required for a person to perform an action that causes the step to be performed is essential. In the GOMS method some standard numerical characteristics are used to estimate mechanical time. However, a hypothesis is put forward, and it is experimentally shown that a statistically significant minimum time for performing actions can be used as mechanical time. This hypothesis was experimentally confirmed. The method and results of this experiment are presented in the article. Developed on this basis, the methodology for assessing the quality of the interface can be used when retraining users in the process of transition of organizations to domestic software in order to evaluate the interfaces.